Effects of nitrogen-doped multi-walled carbon nanotubes compared to pristine multi-walled carbon nanotubes on human small airway epithelial cells. (3rd July 2015) - Mihalchik, Amy L.; Ding, Weiqiang; Porter, Dale W.; McLoughlin, Colleen; Schwegler-Berry, Diane; Sisler, Jennifer D.; Stefaniak, Aleksandr B.; Snyder-Talkington, Brandi N.; Cruz-Silva, Rodolfo; Terrones, Mauricio; Tsuruoka, Shuji; Endo, Morinobu; et al.
Abstract: Nitrogen-doped multi-walled carbon nanotubes (ND-MWCNTs) are modified multi-walled carbon nanotubes (MWCNTs) with enhanced electrical properties that are used in a variety of applications, including fuel cells and sensors; however, the mode of toxic action of ND-MWCNT has yet to be fully elucidated. In the present study, we compared the interaction of ND-MWCNT or pristine MWCNT-7 with human small airway epithelial cells (SAEC) and evaluated their subsequent bioactive effects. Transmission electron microscopy, X-ray photoelectron spectroscopy, Raman spectroscopy, and X-ray diffraction suggested the presence of N-containing defects in the lattice of the nanotube. The ND-MWCNTs were determined to be 93.3% carbon, 3.8% oxygen, and 2.9% nitrogen. A dose–response cell proliferation assay showed that low doses of ND-MWCNT (1.2 μg/ml) or MWCNT-7 (0.12 μg/ml) increased cellular proliferation, while the highest dose of 120 μg/ml of either material decreased proliferation. ND-MWCNT and MWCNT-7 appeared to interact with SAEC at 6 h and were internalized by 24 h. ROS were elevated at 6 and 24 h in ND-MWCNT exposed cells, but only at 6 h in MWCNT-7 exposed cells. Significant alterations to the cell cycle were observed in SAEC exposed to either 1.2 μg/ml of ND-MWCNT or MWCNT-7 in a time and material-dependent manner, possibly suggesting potential damage or alterations to cell cycle machinery. Our results indicate that ND-MWCNT induce effects in SAEC over a time and dose-related manner which differ from MWCNT-7. Therefore, the physicochemical characteristics of the materials appear to alter their biological effects.